STRATEGI PENANAMAN PENDIDIKAN ADAB DI MI TAHFIDZ AL-FURQON PONOROGO - Azid Syukroni (AL-ASASIYYA: Journal Of Basic Education, 2018)
Adab education be a strategic step in preparing the generation because adab education in modern life is becoming very important. This research as an affirmation of the importance of adab education to children from a young age and strategy implementation. Simple and basic things like speaking, eating and respecting others must be well embedded in the child. What is done by MI Tahfidz al-Furqon Ponorogo as adab school and tahfidz be a fresh breeze for the development of the education world in Ponorogo regency?. This research was conducted with qualitative-descriptive approach aimed at describing the existing education model in MI Tahfidz al-Furqon Ponorogo, starting school policy, adab curriculum and implementation strategy. Data collection is done by in-depth interview, observation and documentation. The results show that the parents/guardians and the community are satisfied with the pattern of adab education in MI Tahfidz al-Furqon.